Estimating dynamic panel models: Backing out the Nickell Bias - Jerry A. Hausman; Maxim L. Pinkovskiy (Centre for Microdata Methods and Practice (cemmap), 2017)
We propose a new estimator for the dynamic panel model, which solves the failure of strict exogeneity by calculating the bias in the first-order conditions as a function of the autoregressive parameter and solving the resulting equation. The estimator does well in a wide variety of situations where other estimators do not perform well: stationary initial condition, predetermined but not strictly exogenous regressors, and the presence of correlation between the error terms and the fixed effects. We also propose a general method for including predetermined variables in fixed-effects panel regressions.
Keywords: C01; C22; C23; 330